The non-palindromic adaptor-PCR method for the identification of the T-cell receptor genes of an interferon-gamma-secreting T-cell hybridomaspecific for trans-sialidase, an immunodominant Trypanosoma cruzi antigen - Hiyane,M.I. (2006)
Cloning of the T-cell receptor genes is a critical step when generating T-cell receptor transgenic mice. Because T-cell receptor molecules are clonotypical, isolation of their genes requires reverse transcriptase-assisted PCR using primers specific for each different Valpha or Vß genes or by the screening of cDNA libraries generated from RNA obtained from each individual T-cell clone. Although feasible, these approaches are laborious and costly. The aim of the present study was to test the application of the non-palindromic adaptor-PCR method as an alternative to isolate the genes encoding the T-cell receptor of an antigen-specific T-cell hybridoma. For this purpose, we established hybridomas specific for trans-sialidase, an immunodominant Trypanosoma cruzi antigen. These T-cell hybridomas were characterized with regard to their ability to secrete interferon-gamma, IL-4, and IL-10 after stimulation with the antigen. A CD3+, CD4+, CD8- interferon-gamma-producing hybridoma was selected for the identification of the variable regions of the T-cell receptor by the non-palindromic adaptor-PCR method. Using this methodology, we were able to rapidly and efficiently determine the variable regions of both T-cell receptor chains. The results obtained by the non-palindromic adaptor-PCR method were confirmed by the isolation and sequencing of the complete cDNA genes and by the recognition with a specific antibody against the T-cell receptor variable ß chain. We conclude that the non-palindromic adaptor-PCR method can be a valuable tool for the identification of the T-cell receptor transcripts of T-cell hybridomas and may facilitate the generation of T-cell receptor transgenic mice.